Histopathological study of nasal lesions: 2 years study - Parmar, Nisha Jayantilal; P. Jethwani, Deepa; A. Dhruva, Gauravi (International Journal of Research in Medical Sciences, 2018)
ackground: Majority of the nasal lesions are polypoid. It is difficult to comment upon the nature of the nasal lesion- whether neoplastic or non-neoplastic. Hence histopathological examination is essential for both ENT surgeons as well as pathologists. Aim to study the incidence of different nasal lesion. Also, to find out frequency of inflammatory, benign and malignant conditions of nasal lesions and to compare various histopathological lesions of nasal mass in relation to age, sex and site distribution. Methods: The present study was undertaken in histopathology laboratory of Department of Pathology, P.D.U. medical college and hospital, Rajkot for period of 2 years from October 2013 to September 2015. A histopathological study of total 100 cases of nasal lesions was done. Tissue were processed and studied. Results: Out of 100 cases, 59 were males and 41 were females. Male to Female ratio was 1.44:1. Maximum numbers of nasal lesions were detected in age group of 11-20 years with 24 (24.00%) cases. Out of these 100 cases, 80 (80.00%) were non neoplastic and 20 (20.00%) were of neoplastic origin. In neoplastic lesions, 12(12.00%) were benign, 1 (1.00%) was borderline and 7 (7.00%) were malignant nasal lesions. Non neoplastic lesions were composed of the majority of cases followed by benign neoplastic lesions. Conclusions: Most of malignant neoplastic lesions were occurs after 40 years of age. Incidence of malignant neoplastic lesions was increase with advanced age.